The Arab-Israeli wars : war and peace in the Middle East from the 1948 War of Independence to the present - Herzog, Chaim 1918- (Greenhill Books, 2005)
Tells the epic story of Israel's struggle to exist through the triumphs and tragedies of the first thirty-five years of its life, providing an account of one of history's enduring conflicts - Arab versus Jew. In this book, the author highlights the personal and political struggles that have determined the Middle East conflict.